P18 The role of decompressive craniectomy for traumatic brain injury: should we be leaving the lid off?. Issue 3 (14th February 2019) - Saukila, LF; Little, B; Phillips, NI; Anderson, IA
Abstract : Objectives: The RESCUEicp study has not culminated in consensus about the role of decompressive craniectomy following head injury. Another study (RESCUE-ASDH) also questions craniectomy for patients with ASDH. We examined our own practice over 5 years. Design: Retrospective analysis at a single UK unit. Comparison of outcomes with RESCUEicp results and national data obtained from the Neurosurgical National Audit Programme (NNAP). Subjects: 82 patients over 5 years. 87% male. 90% adults (age >16). Methods: Local data: demographics, CT features, pre-op GCS/pupil reaction/ICP, primary/secondary craniectomy, operative timings, length of stay (critical care/overall), Extended Glasgow Outcome Scores, discharge location. NNAP data analysis. Results: 43% had ASDH with MLS >5 mm (91% primary decompression). Median time to primary surgery from referral 1 h37. 11 primary, 6 secondary decompressions/year; no change over 5 years 3 extensions of craniectomy, 3 had previous craniotomy converted. 30 day mortality 28%. Overall GOS-E: death 33%, lower severe disability 6%, upper severe disability 6%, moderate disability 16%, good recovery 37% (improved by better presentation GCS). 75% had cranioplasty. Median length of stay 41 days. Conclusions: Our practice has not changed over time, despite RESCUEicp. Good outcomes observed may be due to local specialist management of these patients, or reflect judicious case selection. Case-by-case decisions are crucial and may explain why large trials fail to change real-world management strategies. NNAP data comparison ongoing.